Application Absence Online Students: Solutions Reduce Wasted Time Vain - Sutopo Priyanto; Imam Tabroni; Nunung Lesmanasari; Jaja Miharja (Yayasan Adra Karima Hubbi, 2024)
Objective study This is for designing something system for Google Workspace-based online attendance for streamline processes and record absenteeism. Study This uses Method ADDIE development (analysis, Design, Development, Implementation, evaluation) or R&D (Research and development) using data collection techniques (1) Observation, (2) Interview, (3) Questionnaire. Data analysis for know effectiveness absenteeism before and after use application online attendance. Subject study This is 20 students for the testing scale small and 50 remaining schoolgirls for the testing group big. As well as 50 students` pre-test and post-test questionnaire effectiveness system attendance at SMAN 1 Babakan before and after the use application. Research result This is (1) a product application online attendance at SMAN 1 Babakan based Google Workspace (2) Eligibility levels product This is known through evaluation validation two experts and earn results with category Very Appropriate / Very Worthy For aspect material and appearance. The product this is also through trial stage scale small and scale big and both get results evaluation with category very worthy. Thereby can concluded that the product on research development This appropriate for used, and (3) Based on the results questionnaire effectiveness system absenteeism before use application average of 51.28% and after use application SMAN 1 Babakan's online attendance average was 88.72%.